2022
DOI: 10.1590/0004-282x-anp-2022-s106
|View full text |Cite
|
Sign up to set email alerts
|

Headaches and obesity

Abstract: Obesity and headache disorders are two very common conditions in the general population that have been increasing in incidence over the last decades. Recent studies have shown a significant relationship between obesity and headaches, particularly migraine, with an important role in whether the disease is chronic. On the other hand, no such association was found with tension-type headaches. Studies showing an overlapping of hunger-control pathways and those involved in the pathophysiology of migraine may justif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Several biological links between obesity and migraine may explain this observed phenomenon. Previous investigations have revealed a common dysfunction of the hypothalamus and its associated neurotransmitters, 31 and both conditions have been noted to share key proinflammatory mediators, such as interleukin-6, tumor necrosis factor-alpha, and leptin. [32][33][34] Furthermore, obesity has also been shown to alter dural levels of calcitonin gene related peptide and modulate estrogen metabolism, both of which have been linked to migraine pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Several biological links between obesity and migraine may explain this observed phenomenon. Previous investigations have revealed a common dysfunction of the hypothalamus and its associated neurotransmitters, 31 and both conditions have been noted to share key proinflammatory mediators, such as interleukin-6, tumor necrosis factor-alpha, and leptin. [32][33][34] Furthermore, obesity has also been shown to alter dural levels of calcitonin gene related peptide and modulate estrogen metabolism, both of which have been linked to migraine pathology.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity can also contribute to the development of conditions, such as PTS, depression, and cognitive disorders, which may lead to poor academic success 14 . Previous studies reported that obesity was an important risk factor for the PTS development [15][16][17] . In a study involving 165 children in the United States of America, about half of the patients were overweight (23.4%) or obese (33.1%) 18 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a small trial concluded that the ketogenic diet is likely beneficial because it helps people lose weight and migraine sufferers are overweight ( 188 ). Interestingly there are many studies pointing to migraineurs being overweight ( 189 , 190 ), yet my experience in working with thousands of migraine sufferers from around the world is that they are not overweight—in fact many are underweight as a result of being unable to eat while they are so often in pain. Regardless, weight loss on its own is not likely to lead to the reduction of migraine given that it is a genetic condition of ionic channel variants and the brain’s glucose intolerance ( 191 ).…”
Section: The Cause Of Migrainementioning
confidence: 99%